PENGARUH VARIASI PUTARAN SPINDLE DAN FEEDING TERHADAP KEKASARAN PERMUKAAN MATERIAL ALUMUNIUM SERI 6 PADA PROSES SURFACE TURNING MENGGUNAKAN MESIN BUBUT CNC TIPE XTRA – 420 - Arik Indra Pratama; Fajar Satriya Hadi; Basuki Basuki; Mohammad Munib Rosadi (JURNAL ILMIAH NUSANTARA, 2024)
The purpose of this study is to determine the optimal surface roughness level of a Series 6 aluminum workpiece profile by using different spindle speeds and feed rates on a CNC lathe machine. This research used a eksperimental method, which aims to determine conditions and obtain more valid data froms research. The research instrument used a surface roughness tester with a total of 27 test samples. Based on the data obtained from lab tests, the surface roughness results from varying spindle speeds and feeding rates show that at a spindle speed of 1,450 RPM, the lowest roughness achieved at a feeding rate of 0.12 mm/min is 0.90 µm. At a spindle speed of 1,650 RPM, the lowest roughness achieved at the same feeding rate is 0.86 µm. Meanwhile, at a spindle speed of 1,850 RPM, the lowest roughness achieved at a feeding rate of 0.12 mm/min is 0.85 µm.